Lexical-Semantic Features of Epithets - Botyrova Makhliyo; Bozorova Gulshan (Researchparks Publishing, 2022)
The process of developing the oral speech skills of foreign language for linguistic departments of Higher Education is different from the process of developing it for non-philological departments. The process has its own pecularities. The quality of education, which is a bilateral process between the teacher and student, depends on the didactic perfection of teacher`s mastery, and on the other hand, the on the student's motivational activity. Meanwhile, if the high scientific potential and methodological skills of the teacher is integrated with the educational activity of students high results can be achieved in the short term period.